Tourism and the Mediterranean Experience Amidst Environmental Issues: Fresh Insights from Panel Analysis - Bekun, Festus Victor; Dossou, Toyo Amegnonna Marcel; Eluwole, Kayode Kolawole; Lasisi, Taiwo Temitope; Uzuner, Gizem (International Journal of Energy Economics and Policy, 2023)
According to the United Nations World Tourism Organization (UNWTO), tourism is critical to a country’s economic development. It acts as a catalyst for direct and indirect job creation, economic growth, and the attraction of foreign direct investment (FDI). To this end, the present study looks into the relationship between economic growth (GDP), domestic credit (DC), tourism (TR), FDI, and CO2 emissions for selected Mediterranean countries. This study employs panel corrected standard errors (PCSE) and dynamic ordinary least squares (DOLS) approaches to assure the trustworthiness of the findings. The empirical information gathered supports the idea that tourism adds to pollution in the analyzed blocs. Furthermore, the data supports the pollution haven hypothesis concept by demonstrating that an increase in FDI harms the environment. The study’s findings advocate for precautionary actions to alleviate the detrimental effects of tourism-related pollution. Ecotourism policies that support sustainable behaviors must be developed and implemented. Countries can establish a balance between economic growth and environmental protection by implementing such policies. Governments, policymakers, and stakeholders must work together to create effective frameworks and policies that promote responsible tourism. This research fills a knowledge vacuum by shedding light on the specific dynamics of Mediterranean tourism businesses. Economic growth, domestic credit, tourism, FDI, and CO2 emissions are all linked, according to empirical research. The findings highlight the importance of establishing ecotourism legislation and constructing sustainable infrastructure to reduce tourism’s negative environmental impacts. Countries may safeguard the long-term viability of their tourism businesses by finding a balance between economic growth and environmental protection.